Performance and Economic of Production of Broiler Chickens fed Maize and Yam Peels based Diets supplemented with Xylanase, Amylase and Protease Multi-enzymes at starter phase Target audience: Nutritionist, researchers, feed millers and poultry farmers - Oguntoye, M.A.; Hapson, U.; Adamu, F.; Daniel, D.K.; Daniel, B. (Nigerian Journal of Animal Science, 2023)
This study was conducted to investigate the effect of maize and yam peels meal based diets with and without enzyme supplementation on the growth performance and economic of production of broiler chickens at starter phase. One hundred and eighty (180) day old broiler chicks were fed six diets in two groups. The first group of diets contained: maize replaced with yam- peel (YPM) at 0%, 15% and 30 % levels without enzyme supplementation designated as T1, T2 T3 respectively. The second group of diets contained maize replaced with YPM at 0%, 15% and 30% with enzyme supplementation of 50g/kg designated as T4, T5 T6 respectively. Birds were allotted to 6 dietary treatments in a completely randomized design. Each treatment was replicated 3 times consisting of10 chicks per replicate. The experiment lasted for 4 weeks. The results of growth performance showed significant differences (P<0.05) in final weight, weight gain, daily weight gain and feed intake. . Higher l values were recorded for birds fed T1 (control diet) and T6 (diet containing 30% yam peel meal with enzyme supplementation) across the treatments. . Birds fed control diet (T1) and diet containing 30% yam peel meal with enzyme (T6) had higher values of 909.93g and 903.21g respectively for final weight at comparative level to others. However, lower significant (P < 0.05) values were obtained for birds fed T4 (diet containing 0% yam peel meal with enzyme) and T5 (diet containing 15% yam peel meal with enzyme supplementation) across the parameters measured. No significant differences (P > 0.05) in feed conversion ratio. However, operation cost and cost of DOC interaction of yam peel meal and enzyme showed significant difference (P < 0.05) in determining for economic production. The economic analysis revealed that cost in N/kg of diet decreased linearly with increased of level of yam peel meal with and without enzyme supplementation in the diet. Birds fed control diet (T1) and diet contained 0g yam peel meal with enzyme (T4) had higher values for cost of feed consumed per bird, cost of production, feed cost percentage and total cost. The profit margin ranged from N154.80 - N 178.40 for birds fed diet contained 30% yam peel meal with enzyme (T6) having the highest gross margin. Based on the results of this study, it was concluded that yam peel meal can replace maize up to 30% in broiler starter ration with or without enzyme for improved performance with some reduction in the cost of production. .. From economic point of view in term of profit margin, 30% yam peel meal with enzyme supplementation is recommended.